Proliferation of Highly Cytotoxic Human Natural Killer Cells by OX40L Armed NK-92 With Secretory Neoleukin-2/15 for Cancer Immunotherapy - Guo, Meng; Sun, Chen; Qian, Yuping; Zhu, Liye; Ta, Na; Wang, Guangjian; Zheng, Jianming; Guo, Fengfu; Liu, Yanfang (Frontiers in Oncology, 2021)
Adoptive natural killer (NK) cell transfer has been demonstrated to be a promising immunotherapy approach against malignancies, but requires the administration of sufficient activated cells for treatment effectiveness. However, the paucity of clinical-grade to support the for large-scale cell expansion limits its feasibility. Here we developed a feeder-based NK cell expansion approach that utilizes OX40L armed NK-92 cell with secreting neoleukin-2/15 (Neo-2/15), a hyper-stable mimetic with a high affinity to IL-2Rβγ. The novel feeder cells (NK92-Neo2/15-OX40L) induced the expansion of NK cells with a 2180-fold expansion (median; 5 donors; range, 1767 to 2719) after 21 days of co-culture without added cytokines. These cells were highly cytotoxic against Raji cells and against several solid tumors in vivo. Mechanistically, NK92-Neo2/15-OX40L induced OX40 and OX40L expression on expanded NK cells and promoted the OX40-OX40L positive feedback loop, thus boosting NK cell function. Our data provided a novel NK cell expansion mechanism and insights into OX40-OX40L axis regulation of NK cell expansion.